PHENOTYPIC PROFILE AND FUNCTIONAL ACTIVITY OF MONOCYTES IN THE PATIENTS WITH ACUTE PANCREATITIS - A. A. Savchenko; A. G. Borisov; D. E. Zdzitovetskiy; I. V. Kudryavtsev; A. Yu. Medvedev; A. V. Moshev; I. I. Gvozdev (Медицинская иммунология, 2017)
The aim of this study was to evaluate some features of subpopulational profile and functional activity of monocytes in patients with acute pancreatitis. The study included 33 subjects with acute pancreatitis of middle-to-severe degree. Thirty-five healthy age-matched people served as a control group. The study of monocyte phenotype was performed by flow cytometry. Phagocytic ability of monocytes was determined by flow cytometry, by means of FITC-labeled staphylococcal protein A. We assessed percentage of fluorescent monocytes (defined as phagocytic index), like as average cell fluorescence (phagocytic number). The phagocytic indexes were determined for a total monocyte fraction, and well as for distinct cell subpopulations (CD14+CD16- , CD14dimCD16+ и CD14lowCD16+). Intensity of respiratory burst in the monocytes was evauated with chemiluminescence analysis. We used two indicators (lucigenin and luminol) to assess production of primary and secondary reactive oxygen species. In the patients with acute pancreatitis, we have found certain changes in blood monocyte subpopulations and their functional activity. The changes in monocyte subpopulations in acute pancreatitis were characterized by increased numbers of inflammatory cell forms in blood (CD14lowCD16+), along with while near-normal contents of the cells with «classic» (CD14+CD16- ) and «non-classical» phenotype (CD14dimCD16+), having been within reference ranges. It is assumed that high levels of pro-inflammatory monocytes may produce a pathogenetic «circuit» which is characterized by positive mutual stimulation of monocyte-mediated inflammation in local (pancreatic) and blood compartments. Apparent development of such mutual induction of inflammatory events may determine a low efficiency of anti-inflammatory therapy in acute pancreatitis. The functional characteristics of the monocytes in patients with acute pancreatitis are defined as a decrease in phagocytic activity and low respiratory burst intensity. Reduced phagocytic activity of monocytes was detectable in all the cellular subpopulations. Decreased intensity of monocytic respiratory burst in acute pancreatitis depends on low background and induced synthesis of both primary and secondary reactive oxygen species. Thus the patients with acute pancreatitis exhibit imbalanced with respect to synthesis of primary and secondary reactive oxygen species in the monocytes may result from specific action of circulating pancreatic enzymes upon the cells, or due to increased concentrations of pro-inflammatory cytokines. The imbalance between the monocyte subpopulations and reduction of their functional activity in acute pancreatitis may represent an immunopathogenetic basis for development of pancreatic necrosis and sepsis.